SERTIFIKAT HAK MILIK YANG DIPEROLEH PENGGARAP ATAS DASAR SURAT KETERANGAN KEPEMILIKAN DARI DESA: STUDI DI KABUPATEN POHUWATO PROVINSI GORONTALO - Baderan, Yesika Adhisdea; Purwaningsih, Endang; Santosa, Irwan (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
Land Title Certificates are proof of land ownership granted by the Government through the Land Agency to landowners, but in its development there have been Land Title certificates given to someone who is not a land owner (cultivator) based on a Certificate of Land Ownership from the Village. This research was conducted in Marisa Village and Bunto Village, Popayato District, Pohuwato Regency which aims to analyze the legal certainty of the recognition of land ownership certificates by cultivators who bear ownership letters from the village, as well as legal settlements for applications for ownership certificates obtained by cultivators who are not landowners. actually. Research This thesis is a normative-empirical legal research, using statutory, historical, and sociological approaches to examine primary and secondary data. Primary data in this study were obtained through field research by means of interviews, secondary data were obtained through library research, then the data were analyzed qualitatively. The results of the research show that the acquisition of land rights by cultivators as stated in the land ownership certificate from the village does not contain information as to where the cultivators obtained the land from. For dispute resolution, it must be done through the judiciary, because the land has been certified in the name of the cultivator, so an annulment must be requested